Undervisning i förskolan: Holistisk förskoledidaktik byggd på lek och utforskande - Monica Nilsson; Robert Lecusay; Karin Alnervik (Utbildning & Demokrati)
In this article we critically examine and problematize the concept of teaching in contemporary Swedish preschool provision, and sketch a holistic preschool didactics aimed at addressing key problems that emerge from the implementation of the concept of teaching in preschool. We briefly survey how teaching is conceptualized and managed from different theoretical perspectives and institutional discourses. Drawing on cultural historical activity theory and situated learning approaches, we argue for the formation of a preschool didactics based on a socio-cultural understanding of play in combination with a Reggio Emilia-inspired understanding of exploratory and project-based work methods.